Predictive value of trendelenburg position and carotid ultrasound for fluid responsiveness in patients on VV-ECMO with acute respiratory distress syndrome in the prone position - Zhao, Junjie; Sun, Yong; Tang, Jing; Guo, Kai; Zhuge, Jiancheng; Fang, Honglong (Scientific reports, 2024)
Fluid administration is widely used to treat hypotension in patients undergoing veno-venous extracorporeal membrane oxygenation (VV-ECMO). However, excessive fluid administration may lead to fluid overload can aggravate acute respiratory distress syndrome (ARDS) and increase patient mortality, predicting fluid responsiveness is of great significance for VV-ECMO patients. This prospective single-center study was conducted in a medical intensive care unit (ICU) and finally included 51 VV-ECMO patients with ARDS in the prone position (PP). Stroke volume index variation (ΔSVI), pulse pressure variation (PPV), stroke volume variation (SVV), baseline carotid corrected flow time (FTc Baseline ), and respirophasic variation in carotid artery blood flow peak velocity (ΔVpeak CA ) were taken before and after the Trendelenburg position or volume expansion. Fluid responsiveness was defined as a 15% or more increase in stroke volume index as assessed by transthoracic echocardiography after the volume expansion (VE). In our study, 33 patients (64.7%) were identified as fluid responders. Stroke volume index variation induced by the Trendelenburg position (ΔSVI Trend ), FTc Baseline , and ΔVpeak CA demonstrated superior predictive performance of fluid responsiveness. ΔSVI Trend had an AUC of 0.89 (95% CI, 0.80–0.98) with an optimal threshold of 14.5% (95% CI, 12.5–21.5%), with the sensitivity and specificity were 82% (95% CI, 66–91%) and 83% (95% CI, 61–94%). FTc Baseline had an AUC of 0.87 (95% CI, 0.76–0.98) with an optimal threshold of 332ms (95% CI, 318-335ms), the sensitivity and specificity were 85% (95% CI, 69–93%) and 83% (95% CI, 61–94%), respectively. ΔVpeak CA showed an AUC of 0.83 (95% CI, 72–95), with a 10% optimal threshold (95% CI, 9–13%), sensitivity was 82% (95% CI, 66–91%) and specificity 78% (95% CI, 55–91%). ΔSVI Trend , FTc Baseline and ΔVpeak CA could effectively predict fluid responsiveness in VV-ECMO patients with ARDS in the PP. Compared to ΔSVI Trend and ΔVpeak CA , FTc Baseline is easier and more direct to acquire, and it does not require Trendelenburg position or VE, making it a more accessible and efficient option for assessing fluid responsiveness.